The antibacterial activity of clove Syzygium aromaticum extract and its effects on the survival rate of hybrid grouper Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂ infected with Vibrio alginolyticus - Ode, Inem; Sukenda; Widanarni; Dinamella Wahjuningrum; Munti Yuhana; Mia Setiawati (Indonesian Society of Scientific Aquaculture (ISSA), 2023)
Vibrio alginolyticus which becomes the main cause of vibriosis disease in grouper culture and causes great economic loss in Asian aquaculture industries. This study investigated the antibacterial activity of clove extract and the effect of adding clove powder to the diet on survival cantang grouper infected with V. alginolyticus. The clove extraction used a maceration method. Two dose levels of clove powder were used, namely 10 and 15 g kg−1. The control treatments without clove powder supplementation contained positive control (CP) and negative control treatment (CN). The results found that the clove extract contained five major compounds. The highest compound was phenol, 2-methoxy-4-(2-propenyl)-Eugenol (64.07%). Phytochemical analysis of clove extract contained phenolics, flavonoids, and tannins at (28.53 ± 0.00) mg/g, (0.38 ± 0.00) mg/g, and (0.15 ± 0.00) %, respectively. The diameter of the clove extract inhibition zone was significantly different (P < 0.05) in all treatments. The Scanning Electron Microscopy (SEM) result presents that the clove extract can alter the V. alginolyticus cell morphology. The dietary supplementation of clove powder improves the survival rate significantly higher (P<0.05) post-challenge test. The conclusion of this research is that clove extract has antibacterial activity that can inhibit growth and cause cell morphological damage to V. alginolyticus. The application of clove powder at a dose of 15g kg-1 was able to improve the survival value which was a higher post-challenge test. Keyword: antibacterial activity, clove, grouper, phytochemical, Vibrio alginolyticus